Daily life changes and adaptations investigated in 154 families with a child suffering from a rare disability at a public centre for rare diseases in Northern Italy. Issue 1 (December 2016) - Silibello, G.; Vizziello, P.; Gallucci, M.; Selicorni, A.; Milani, D.; Ajmone, P.; Rigamonti, C.; De Stefano, S.; Bedeschi, M.; Lalatta, Faustina
Abstract Background Living with a disabled child has profound effects on the entire family. With a prevalence of developmental disabilities around 2, 5 %, there is a considerable need to promote improvements in the health care system. Little is known about changes and adaptations in the lives of affected families and this paucity of information hinders the improvement of services. This study sought to explore the needs and changes in the everyday life of families with children suffering from rare diseases of varying severity, with and without mental disability. The aim was to measure the socio-demographic characteristics, health care problems and living conditions of a large cohort of families with an affected member. Methods A sample of 154 families was recruited between September 2011 and April 2013 to respond to a 136 item questionnaire that explored different areas of concern (diagnosis and follow-up of clinical specialists, relationship with pediatrician, rehabilitation, school, work, institutional and/or private support, child care needs and family relationships). Results All parents answered the questionnaire. They were satisfied with the services provided in particular for diagnosis and follow-up, relationships with the family pediatrician, rehabilitation services and school, regardless of the severity of condition, presence of intellectual disability (ID) or absence of diagnosis. Negative scores were reported for institutional and/or private support and family relationships in severe conditions. Conclusions The Health Care System should maintain a family-centered care and a multi-agency working, improving quality of life of families with disabled child to allow adaptation. At present these services are uncoordinated and financial support is poor, resulting in a heavy burden for these families.